ChemInform Abstract: Polyoxometalates as Versatile Enzyme Inhibitors. Issue 44 (14th October 2013) - Stephan, Holger; Kubeil, Manja; Emmerling, Franziska; Mueller, Christa E.
Abstract Review: 50 refs.